2018
DOI: 10.1080/09585192.2018.1428722
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of global teams for international organizations: HR implications

Abstract: In this special issue we aim to advance the theoretical, conceptual and empirical knowledge about the relationship between global teams and human resource management in international organizations. We argue that although the prevalence of global teams in international organizations is rapidly rising, simultaneously affecting the management of firms on global, regional and local levels, the response of firms and scholars alike to such changes has been slower, especially in the area of IHRM. The HR function in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
0
25
0
3
Order By: Relevance
“…(Audra I. Mockaitis, 2018) -Relocation may negatively impact the DC if LDC starts to use transferred knowledge and skills to initiate its own production and compete with the GTC. Samsung vs. Apple would be a good example of patent infringement -The best students from the top-ranked universities in DCs tend to work in a sensitive sector, most likely drawn by higher salaries.…”
Section: Facts and Assumptionsmentioning
confidence: 99%
“…(Audra I. Mockaitis, 2018) -Relocation may negatively impact the DC if LDC starts to use transferred knowledge and skills to initiate its own production and compete with the GTC. Samsung vs. Apple would be a good example of patent infringement -The best students from the top-ranked universities in DCs tend to work in a sensitive sector, most likely drawn by higher salaries.…”
Section: Facts and Assumptionsmentioning
confidence: 99%
“…GVTs have the potential to provide organizations with a powerful tool to be more flexible in keeping up with rapid changes in the business environment (Mockaitis, Zander & De Cieri, 2018). A recent survey of 1,620 business respondents from 90 countries found that 89% worked on at least one virtual team and 62% stated they work on a team with three or more cultures (RW3 CultureWizard, 2016).…”
Section: Leaders Of Global Virtual Teams: Implications For the Identimentioning
confidence: 99%
“…A recent survey of 1,620 business respondents from 90 countries found that 89% worked on at least one virtual team and 62% stated they work on a team with three or more cultures (RW3 CultureWizard, 2016). While virtual teams assist in creating a positive climate of diversity, they also present their own predicaments in regards to how to effectively lead a team that is culturally diverse and works in various times zones (Mockaitis et al, 2018).…”
Section: Leaders Of Global Virtual Teams: Implications For the Identimentioning
confidence: 99%
See 2 more Smart Citations